Encyclical letter Fratelli tutti of the Holy Father Francis on fraternity and social friendship - Francis, Pope, 1936- (Vaticano: Libreria Editrice Vaticano, 2020)
This powerful encyclical is Pope Francis' "cry from the heart" to all people of the earth to see beyond their differences--indeed to work with their differences--and begin to grow together to build a new and peaceful world. This remarkable document comes from a pastor's heart, setting forth Francis' vision for a new church and new world, against the backdrop of a catastrophic pandemic that has spared nothing and altered everything. Returning again and again to themes he has developed throughout his papacy, Pope Francis speaks of the need for equality and justice for all, cooperation, caring for the most vulnerable, doing the hard work of learning to listen to and accompany others, and caring for the earth that nurtures and sustains us all. Read slowly and reflectively, Pope Francis' message here is full of divine and human wisdom for every person
Fratelli tutti ; Without borders -- 1. Dark clouds over a closed world. Shattered dreams -- 2. A stranger on the road -- 3. Envisaging and engendering an open world -- 4. A heart open to the world -- 5. A better kind of politics -- 6. Dialogue and friendship in society -- 7. Paths of renewed encounter -- 8. Religions and the service of fraternity in our world -- a prayer to the Creator -- An ecunemical Christian prayer.
"Libreria Editirice Vatinica."
Includes bibliographical references.
Keywords: Catholic Church -- Doctrines -- Papal documents; Common good -- Religious aspects -- Catholic Church; Solidarity -- Religious aspects -- Catholic Church; Christian sociology -- Catholic Church; Christian sociology -- Catholic Church; Common good -- Religious aspects -- Catholic Church; Solidarity -- Religious aspects -- Catholic Church